458PMutation tracking in circulating tumour DNA predicts relapse in completely resected EGFR-mutated NSCLC. (24th November 2019) - Filipits, M; Hochmair, M J; Buder, A; Watzka, S
Abstract: Background: Analysis of ctDNA in operable NSCLC for the identification of patients at high risk of relapse could allow tailoring of adjuvant therapy with EGFR tyrosine kinase inhibitors (TKIs). We assessed whether tracking of EGFR mutations in plasma circulating tumor DNA (ctDNA) predicts relapse in completely resected EGFR-mutant NSCLC. Methods: A prospective cohort of 45 EGFR-mutant stage I-IIIB NSCLC patients, all of whom underwent complete resection of their tumors, had plasma samples for ctDNA analysis taken post-surgery and in follow-up. Cobas EGFR Mutation Test (cobas) was used for tissue genotyping of the baseline tumor biopsy or surgical specimens, and droplet digital PCR (ddPCR) was performed to track the identified EGFR mutations in ctDNA. Results: We identified EGFR exon 19 deletions (n = 23), L858R (n = 18), and L861Q (n = 4) mutations by cobas in pre-surgical tissue biopsies and/or surgical specimens, and used ddPCR assays for each EGFR mutation to measure ctDNA after surgery. Detection of ctDNA after complete tumor resection in 11 of 45 (24%) patients significantly predicted clinical relapse (hazard ratio [HR] 7.0, 95% confidence interval [CI] 2.13 to 22.68; log-rank p = 0.001). Multivariable analysis demonstrated that detection of ctDNA remained a significant predictor of clinical relapse after adjusting for clinical factors (HR 6.16, 95% CI 1.80 to 21.06; p = 0.004). Notably, ctDNA-based molecular relapse demonstrated a lead time of up to 8.1 months over clinical relapse. Conclusions: Tracking of EGFR mutations in cfDNA following surgical treatment can identify NSCLC patients at high risk of relapse. Whether ctDNA monitoring could allow tailoring of adjuvant therapy with EGFR tyrosine kinase inhibitors will have to be determined in future clinical trials. Legal entity responsible for the study: The authors. Funding: AstraZeneca. Disclosure: M. Filipits: Honoraria (self), Advisory / Consultancy, Research grant / Funding (self): AstraZeneca; Honoraria (self), Advisory / Consultancy: Boehringer Ingelheim. M.J. Hochmair: Honoraria (self), Advisory / Consultancy: AstraZeneca; Honoraria (self), Advisory / Consultancy: Boehringer Ingelheim. A. Buder: Honoraria (self): AstraZeneca. All other authors have declared no conflicts of interest.